Predictors of Counseling Students' Decision to Pursue a Gerocounseling Specialization. Issue 2 (October 2014) - Foster, Thomas W.; Evans, Ariann N.; Chew, Lisa A.
<x xml:space="preserve">Abstract</x> The authors examined which variables predicted the likelihood of counseling students' decision to pursue a gerocounseling specialization by using logistic regression analysis. Results found that overall interest, perceived preparation, training willingness, and importance were predictive factors. Curriculum strategies on how to implement these variables into existing counselor education course work are discussed.